2018
DOI: 10.1192/bjp.2018.74
|View full text |Cite
|
Sign up to set email alerts
|

Child abuse potential in mothers with early life maltreatment, borderline personality disorder and depression

Abstract: History of ELM as well as the common sequelae, BPD and MDD, pose risks for child abuse. Our findings suggest improvement of emotion regulation as a potential target for intervention programs. These programs should also aim at non-substantiated cases because even an elevated abuse potential affected child mental health.Declaration of interestNone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 27 publications
0
11
0
2
Order By: Relevance
“…Indeed, some studies have shown that major depressive disorder poses a risk for child abuse ( 40 ) while some symptoms frequently occurring in anxiety and major depressive disorder are also associated with child neglect ( 37 , 38 , 41 ). Hence, the risk for mental disorders in both parents and the child caused by the child's CHD could partly explain the higher prevalence of emotional abuse and neglect reported in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, some studies have shown that major depressive disorder poses a risk for child abuse ( 40 ) while some symptoms frequently occurring in anxiety and major depressive disorder are also associated with child neglect ( 37 , 38 , 41 ). Hence, the risk for mental disorders in both parents and the child caused by the child's CHD could partly explain the higher prevalence of emotional abuse and neglect reported in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, parental factors and especially a problematic mother-daughter relationship put children at a greater risk for sexual abuse (43). As we have discussed above, some studies have shown that maternal major depressive disorder and specific psychiatric symptoms classified in the mood and anxiety spectrum are associated with a higher risk for abuse of the respective child (37,38,40,41). Sharing this common factor, namely a possible hazardous and problematic motherchild relationship, the increased prevalence identified in our study may be partly associated with this relationship's structure.…”
Section: Parental Factorsmentioning
confidence: 97%
“…Individuals with BPD show a different pattern of difficulties in controlling their attention: they show a focus on current distress and signals of threat and anger (Baer et al ., 2012), as well as emotional hyper-reactivity with respect to interpersonal situations (Sauer et al ., 2014). In the unfortunate combination with difficulties in emotional regulation which is often shown by patients with BPD in particular but also those with rMDD (Dittrich et al ., 2018 a ), personal distress levels may rise. This is relevant because personal distress may lead to social impairments and interpersonal problems due to unfavorable reactions, such as stress, withdrawal, and non-social behavior, to these emotional situations (Schreiter et al ., 2013; Singer and Klimecki, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…This study was performed within the framework of the UBICA (Understanding and Breaking the Intergenerational Cycle of Abuse, ) multicenter project in Berlin and Heidelberg (Dittrich et al ., 2018 a ; 2018 b ; Kluczniok et al ., 2018). The present study included 251 mothers and their children aged between 5 and 12 years.…”
Section: Methodsmentioning
confidence: 99%
“…Insbesondere für physische sowie emotionale Gewalt und Vernachlässigung zeigt sich ein Zusammenhang mit BPS-Symptomen bei den jugendlichen Nachkommen (Kurdziel et al 2018). Das erhöhte Risiko für Kindesmissbrauch hängt sowohl mit eigenen Missbrauchserfahrungen (Dittrich et al 2018) als auch mit Schwierigkeiten in der Emotionsregulation (Hiraoka et al 2016) der Mütter mit BPS zusammen. Wichtig ist jedoch auch der Befund, dass die berichteten Gewalterfahrungen der Kinder und Jugendlichen nicht ausschließlich von den Müttern mit BPS ausgehen (Kurdziel et al 2018;Macfie und Kurdziel 2019).…”
Section: Epigenetische Mechanismenunclassified